Age-related changes in the human primary motor cortex: A macroscopic and microscopic study - George, Anne; K, Usha K (Asian Journal of Medical Sciences, 2021)
Background: Cerebral hemisphere has outer gray matter and inner white matter. The cerebrum is folded into gyri and sulci in order to accommodate it in the skull. The thickness of the gray matter varies at sulci and gyri and the mean thickness may be from 1.5 mm to 4.0 mm. Aims and Objectives: (1) To demonstrate the cells and laminar architecture of the primary motor cortex with different stains. (2) To find out the age-related changes in the thickness of the primary motor cortex and the depth of the central sulcus. Materials and Methods: Cross-sectional study was done using 50 adult human brains and 10 fetal brains obtained from the Department of Forensic medicine and OBG, respectively, in a Government Medical College in Kerala during 2001–2003. At autopsy, the central sulcus and the precentral gyrus were identified. Depth of central sulcus and thickness of precentral gyrus, in upper, middle, and lower parts were measured using Vernier calipers. Tissue specimens were taken from the precentral gyrus and after fixation in 10% formalin, hematoxylin, and eosin-stained slides were prepared and viewed under a light microscope identifying six laminae. Using an oculo micrometer, width of the six laminae were measured. Pyramidal cells and stellate cells were observed and their size measured. Results: Depth of the central sulcus was more on the right side but it was minimal on the middle part of both sides. The thickness of the precentral gyrus varied from 1 to 6 mm. Maximum thickness of 6 mm was found in the middle and lower parts in the 21–30 age group. Lamina 5 was the widest of all laminae. Maximum width of 1000 μ was noted in the 41–50 age group. Conclusion: Grey matter thickness of 1-6 mm noted in this study was comparable with other studies. Pyramidal cells of varying sizes were seen in all sections with different staining methods. It was confirmed that neuronal loss is inevitable as age advances.